Australasian microtektites across the Antarctic continent: Evidence from the Sør Rondane Mountain range (East Antarctica) - Bastien Soens; Matthias van Ginneken; Stepan Chernonozhkin; Nicolas Slotte; Vinciane Debaille; Frank Vanhaecke; Herman Terryn; Philippe Claeys; Steven Goderis (Geoscience Frontiers, 2021)
The ~790 ka Australasian (micro)tektite strewn field is one of the most recent and best-known examples of impact ejecta emplacement as the result of a large-scale cratering event across a considerable part of Earth's surface (>10% in area). The Australasian strewn field is characterized by a tri-lobe pattern consisting of a large central distribution lobe, and two smaller side lobes extending to the west and east. Here, we report on the discovery of microtektite-like particles in sedimentary traps, containing abundant micrometeorite material, in the Sør Rondane Mountain (SRM) range of East Antarctica. The thirty-three glassy particles display a characteristic pale yellow color and are predominantly spherical in shape, except for a single dumbbell-shaped particle. The vitreous spherules range in size from 220 to 570 μm, with an average diameter of ~370 μm. This compares relatively well with the size distribution (75–778 μm) of Australasian microtektites previously recovered from the Transantarctic Mountains (TAM) and located ca. 2500–3000 km from the SRM. In addition, the chemical composition of the SRM particles exhibits limited variation and is nearly identical to the ‘normal-type’ (i.e., <6% MgO) TAM microtektites. The Sr and Nd isotope systematics for a single batch of SRM particles (n = 26) strongly support their affiliation with TAM microtektites and the Australasian tektite strewn field in general. Furthermore, Sr isotope ratios and Nd model ages suggest that the target material of the SRM particles was composed of a plagioclase- or carbonate-rich lithology derived from a Paleo- or Mesoproterozoic crustal unit. The affiliation to the Australasian strewn field requires long-range transportation, with estimated great circle distances of ca. 11,600 km from the hypothetical source crater, provided transportation occurred along the central distribution lobe. This is in agreement with the observations made for the Australasian microtektites recovered from Victoria Land (ca. 11,000 km) and Larkman Nunatak ...